Speech at the 2017 SHE-ERA Conference - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, emphasized that the Group sees advancement of women as critical to achieving the ending of extreme poverty and boosting shared prosperity. He discussed the need to overcome constraints faced by women. He discussed a variety of World Bank Group projects helping women entrepreneurs as well as raising women’s labor force participation and productivity.